2017
DOI: 10.1038/s41598-017-17148-w
|View full text |Cite
|
Sign up to set email alerts
|

Whitening and Impaired Glucose Utilization of Brown Adipose Tissue in a Rat Model of Type 2 Diabetes Mellitus

Abstract: Brown adipose tissue (BAT) is an attractive therapeutic target to combat diabetes and obesity due to its ability to increase glucose expenditure. In a genetic rat model (ZDF fa/fa) of type-2 diabetes and obesity, we aimed to investigate glucose utilization of BAT by 18F-FDG PET imaging. Male Zucker diabetic fatty (ZDF) and Male Zucker lean (ZL) control rats were studied at 13 weeks. Three weeks prior to imaging, ZDF rats were randomized into a no-restriction (ZDF-ND) and a mild calorie restriction (ZDF-CR) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…Recently, it has been suggested that diet‐induced obesity might cause functional hypoxia in BAT ultimately leading to a functional shift from thermogenesis toward lipid storage . Our data exploring BAT content and gene expression resonate with previous studies showing that exposure to hypercaloric diets enlarges the interscapular BAT depot and does not alter Ucp‐1 or Cidea expression but reduces the expression of Pgc‐1α , suggesting an impaired mitochondrial function upon caloric overload. As previously stated, there is consensus about the potential of Foxc2 in counteracting diet‐induced insulin resistance .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, it has been suggested that diet‐induced obesity might cause functional hypoxia in BAT ultimately leading to a functional shift from thermogenesis toward lipid storage . Our data exploring BAT content and gene expression resonate with previous studies showing that exposure to hypercaloric diets enlarges the interscapular BAT depot and does not alter Ucp‐1 or Cidea expression but reduces the expression of Pgc‐1α , suggesting an impaired mitochondrial function upon caloric overload. As previously stated, there is consensus about the potential of Foxc2 in counteracting diet‐induced insulin resistance .…”
Section: Discussionsupporting
confidence: 89%
“…In basal conditions, brown adipocytes have the ability to release energy as heat in a process mediated by UCP-1 (21). Recently, it has been suggested that diet-induced obesity might cause functional hypoxia in BAT ultimately leading to a functional shift from thermogenesis toward lipid storage (22,23). Our data exploring BAT content and gene expression resonate with previous studies showing that exposure to hypercaloric diets enlarges the interscapular BAT depot (22,23) and does not alter Ucp-1 or Cidea expression (23,24) but reduces the expression of Pgc-1α (24), suggesting an impaired mitochondrial function upon caloric overload.…”
Section: Discussionmentioning
confidence: 99%
“…Because obesity has been associated with structural and functional “whitening” of brown adipose depots in rodents (1114), we performed experiments to confirm that the tissue expansion in SM/J mice has the expected properties of brown fat. Histological analysis of the fat depot taken from high fat-fed SM/J mice at 30 weeks of age confirms the adipocytes in this expansion are brown adipocytes, with small multilocular lipid droplets and high UCP1 staining ( Supplemental Figure 3C-J ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the secreted proteins were detected in cell culture media from both brown and white adipocytes ( Figure 1G), but interestingly, vascular endothelial growth factor A (VEGFA) was only identified in the media from brown adipocytes while leptin (LEP) was exclusively identified in white adipocytes (Table S1). This provides proof of concept of our experimental workflow as LEP is one of the most studied white fat-derived hormones (Stern et al, 2016) while VEGFA is a wellestablished brown fat growth factor (Park et al, 2017;Shimizu et al, 2017).…”
Section: The Secretome Of Human Brown and White Adipocytesmentioning
confidence: 68%